SAT0534 Thrombosis and Re-Thrombosis Manifestations in Patients with Behçet Disease. Descriptive Analysis from Regeb Cohort. (9th June 2015) - Rodríguez Carballeira, M.; Espinosa, G.; Mejía, J.; Solans, R.; Larrañaga, J.; Castillo, M.; Rios, R.; Nieto, J.; Solanich, X.; Fonseca, E.; Muñoz, F.; Fraile, G.; et al.
Abstract : Objectives: To describe the main characteristics of patients with Behçet's disease (BD) who presented with thrombosis included in the Spanish BD Registry Group (REGEB) and try to identify the prognostic factors associated with re-thrombosis in this cohort. Methods: Up to December 2014, 541 BD patients from 20 Spanish hospitals had been included in the REGEB. We selected those patients who presented thrombotic manifestations. Descriptive analysis was performed and factors related with thrombosis recurrence were identified. This project was performed, on behalf of Systemic Autoimmune Diseases Group (GEAS) of the Spanish Society of Internal Medicine (SEMI). This registry started in 2009, with a multicenter, consecutive, and retrospective design. Results: Among 541 BD patients, 85 (16%) had thrombosis. Sixty (70.6%) were men and the mean age of onset of the disease was 27.4 years (11) and median follow-up time was 160 months (range 0-418). Most patients (88.2%) were Caucasian. In 28 (32.9%) cases, HLA B51 was detected. In 36 (42.3%) patients, thrombosis was one of the presenting manifestation of BD and it concurred with other symptoms of BD in 71 (84%). Deep venous thrombosis in the legs (n=49) wasthe most frequent thrombosis followed by cerebral venous sinus thrombosis (n=10). Considering therapy, 68 (80%) patients received anticoagulation, 45 (52.9%) corticosteroids, 25 (29.4%) immunosuppressants and 2 (2.4%) infliximab. During follow-up, 18 (21%) patients presented a second episode of thrombosis and 5 (5.9%) a third. The median time between thrombosis was 26 months (range 1-260). Deep venous thrombosis in the legs was the most frequent (n=13), followed by inferior vena cava thrombosis (n=4), cerebral venous sinus thrombosis (n=3), stroke (n=2), and right ventricle thrombosis (n=1). Other concurrent symptoms of BD were seen in 87% of these events. Treatment at the moment of rethrombosis was anticoagulation in 5; corticosteroids in 9, and immunosuppressants in 5. Rethrombosis was treated with anticoagulants in 20 (87%) cases, corticosteroids in 11 (48%), immunosuppressants in 7 (30%) and adalimumab in one (1%) case. Univariate analysis showed significant association between rethrombosis and central nervous system (CNS) involvement, but it appears unrelated to other clinical signs, gender, use of immunosuppressants or anticoagulation at the moment of the thrombotic event. The Cox multivariate analysis confirmed the relation between rethrombosis and CNS involvement (p=0.26; HR 3.1 CI95% 1.1-8.4) Conclusions: In the REGEB cohort, thrombosis was present in 16% of patients and re-thrombosis in 3.3%, respectively. Re-thrombosis was accompanied by other symptoms of disease activity in the majority of cases and were associated with CNS involvement. Prevalence of immunossupressant agents was no different in patients with rethrombosis. Of note, re-thrombosis occurred in one-fifth of patients receiving anticoagulation. Disclosure of Interest: None declared